EVALUATION OF IMMUNOLOGICAL MARKER INTERLEUKIN-17 AMONG PATIENTS WITH DERMATOPHYTOSIS INFECTION - Saud Obais, Emad; Sami Alammar, Professor. Dr. Fadhil; Jasim Mohammed Ali, Professor. Dr. Angham (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
This study was conducted to evaluates the immunological parameter IL-17) associated with development of dermatophyte infection. The study was carried out in the period beginning of December 2022 to end of June 2023.This study has been done at the Al-Hilla Teaching Hospital, Dermatology Unit, Babylon Government; ages range between 1 to 50 years in male and female. During the study a total 90 clinical specimens (Skin scraping and 5ml of blood) were obtained from all participants (45 dermatophytosis cases and 45 controls). Blood samples (serum introduced for evaluation of concentration level of IL-17 by ELISA. The ELISA was used to measure two types of cytokines (IL-17 and TNF-), and it was observed a significant increase ( P 0.0001 ) of serum IL-17 in dermatophyte infected patients (35.015 0.837 pg/ml) when compared with control subjects (6.481 0.848 pg/ml). The levels of IL-17 concentration in patients Infected with Dermatophyte Infection according to age groups appear non significant difference between age groups (P.value 0.8780) and the highest concentration level of IL-17 appears with age group (31-40 years) and (41-50 years) and were (37.191 2.806 Pg/ml) and (37.006 0.934 Pg/ml) respectively while the lowest concentration level of IL-17 with ( 10 years) was (33.784 4.756 Pg/ml). while in control group, appear non significant difference between age groups (P.value 00.8991) and the highest concentration level of IL-17 appears with age group (51-60 years) and ( 10 years) and were (8.636 2.300 Pg/ml) and (8.281 1.352 Pg/ml) respectively while the lowest concentration level of IL-17 with (31-40 years) was (5.869 1.002 Pg/ml). In depending on Gender, in dermatophyte infected patients group, the results have shown the high concentration level of IL-17 appear in male was (35.950 ± 0.916 Pg/ml) other than female (33.255 1.643 Pg/ml) with non significant difference (P.value 0.1266) also in control group , the results have shown the high concentration level of IL-17 appears in male was (7.383 0.911 Pg/ml) and the low concentration level appears in female and was (6.544 0.957 Pg/ml) , and this height also non significance (P.value 0.5381). The concentration level of IL-17 according to duration of infection in dermatophytosis patients, appear significant difference between groups (P.value 0.0001) and the highest concentration level of IL-17 appears with groups ( 2 years) and was (74.083 9.807 Pg/ml), while the lowest concentration level of IL-17 with (6 month) and was (33.892 2.890 Pg/ml).